First record of potentially toxic dinoflagellate, Alexandrium minutum Halim 1960, from Peruvian coastal - Baylón, Maribel (2015)
Herein, we report the first record of the potentially toxic dinoflagellate Alexandrium minutum Halim 1960 from the Peruvian littoral. Alexandrium minutum produced the algae bloom in March 2006 and February 2009, in the Callao bay. Its identification was carried out by a morpho-taxonomic examination, detailing their plates with light and epifluorescence microscopy, moreover its quantification was realized in sedimentation chambers. This is the first report of A. minutum for Southeast Pacific. The characteristics in size, shape and thecal morphology were similarly to original descriptions of this species.